Integration of Islamic Values in Enhancing Mental Health Awareness and Literacy Among Muslim Adolescents - Amelia Putri Darwiyani; Merry Maharani; Solehatun Anisa (IQTIDA : Journal of Da'wah and Communication, 2024)
The mental health of Muslim adolescents has become a global concern in efforts to improve the well-being of the younger generation. This paper explores integrating Islamic values to enhance mental health awareness and literacy among Muslim adolescents. In this context, Islamic values that promote concern for mental well-being, such as patience (sabr), gratitude (shukr), and mutual assistance (ta'awun), are the primary focus of this research. Using a qualitative approach, this study involves literature analysis and an in-depth understanding of Islamic teachings relevant to mental health. The results indicate that integrating Islamic values into education and mental health interventions can significantly increase Muslim adolescents' awareness of the importance of self-care and addressing mental health issues. The implication of this study highlights the importance of a holistic and culturally grounded approach in strengthening mental health prevention and intervention efforts among Muslim adolescents. In conclusion, the integration of Islamic values can serve as a strong foundation for promoting mental health awareness and literacy, as well as improving overall well-being among Muslim adolescents.